2013
DOI: 10.1371/journal.pone.0057550
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny as a Proxy for Ecology in Seagrass Amphipods: Which Traits Are Most Conserved?

Abstract: Increasingly, studies of community assembly and ecosystem function combine trait data and phylogenetic relationships to gain novel insight into the ecological and evolutionary constraints on community dynamics. However, the key to interpreting these two types of information is an understanding of the extent to which traits are phylogenetically conserved. In this study, we develop the necessary framework for community phylogenetics approaches in a system of marine crustacean herbivores that play an important ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 73 publications
(89 reference statements)
2
31
0
Order By: Relevance
“…1a), here we found that at least one of those species (P. cowani) may be negatively affected by even the 18°C average temperature on the harbour mudflats where much of the Ulva is found (Fig. However, in our previous measurements of temperature tolerance, we found high correspondence between effects of constant high temperature and tidal-scale temperature variation (Best & Stachowicz, 2013). This experiment did exclude the variation around this mean that would naturally be found in the harbour, and such variation can have important consequences for survival and feeding rates (Sanford, 2002;Clusella-Trullas et al, 2011;Marshall & McQuaid, 2011).…”
Section: Variation Among Grazer Speciessupporting
confidence: 59%
See 1 more Smart Citation
“…1a), here we found that at least one of those species (P. cowani) may be negatively affected by even the 18°C average temperature on the harbour mudflats where much of the Ulva is found (Fig. However, in our previous measurements of temperature tolerance, we found high correspondence between effects of constant high temperature and tidal-scale temperature variation (Best & Stachowicz, 2013). This experiment did exclude the variation around this mean that would naturally be found in the harbour, and such variation can have important consequences for survival and feeding rates (Sanford, 2002;Clusella-Trullas et al, 2011;Marshall & McQuaid, 2011).…”
Section: Variation Among Grazer Speciessupporting
confidence: 59%
“…These mesograzers play a key role in controlling blooms of benthic algae and facilitating the growth of seagrasses, which are key habitat providers in coastal and estuarine systems (Duarte, 2002;Valentine & Duffy, 2006;Best & Stachowicz, 2012;Whalen et al, 2013). However, the species from the outer coast can survive in increased water temperatures (25°C, nearing the maximum temperatures reached at shallow harbour sites at low tide) for longer than several species that are currently found in Bodega Harbor, including both native species and successful exotic colonists (Best & Stachowicz, 2013; data summarized in Fig. and/or seagrasses, and they consume Ulva in feeding trials (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, applying this approach to conservation biology (Asmyhr, Linke, Hose, & Nipperess, ) and local community ecology (Elbrecht & Leese, ; Jones, Ghoorah, & Blaxter, ) can be risky. OTUs of unknown vulnerability to different threats lack protection, and their ecological role in local assemblages cannot be inferred from phylogenetic relatedness alone (Best, Caulk, & Stachowicz, ; Best & Stachowicz, , ; Kembel, ).…”
Section: Cryptic Diversity In Biodiversity Researchmentioning
confidence: 99%
“…However, the underlying assumption that phylogenetic diversity serves as a proxy for trait differentiation is not always supported; in some cases, phylogenetic diversity influences ecosystem structure and functioning even when phylogenetic distance is not correlated with trait differences (Flynn et al., 2011; Tan, Pu, Ryberg & Jiang, 2012). Furthermore, not all traits relevant to the outcome of interactions are evolutionarily conserved (Best, Caulk & Stachowicz, 2013; Best & Stachowicz, 2013; Cavender‐Bares, Ackerly, Baum & Bazzaz, 2004; Cavender‐Bares, Keen & Miles, 2006; Moles et al., 2005; Silvertown, Dodd, Gowing, Lawson & McConway, 2006) and phylogenetic distance does not always influence ecological processes in the expected direction (Burns & Strauss, 2011; Cadotte, Davies & Peres‐Neto, 2017; Godoy, Kraft & Levine, 2014; Narwani, Alexandrou, Oakley, Carroll & Cardinale, 2013). …”
Section: Introductionmentioning
confidence: 99%